Properties Of Graphene And Its Application On Electronic Industries–A Review - Salim, Mohd Azli; Md. Saad, Adzni; Termiti, Zarif Hasif; Omar, Ghazali (Universiti Teknikal Malaysia Melaka, 2018)
Graphene popularity is rapidly increasing due to the unique structural,excellent functional properties and also wide range of application in many industries. Graphene is an amazing man-made two-dimension (2D) with single atom thick material ever made in this world.It is the most lightweight material that has been discovered, which consists of a monolayer of sp^2 hybridized carbon atoms in two-dimensional (2D) hexagonal crystal structure.From past research,it was stated that graphene is useful in any industries especially in electronic industry.The aim of this paper is to discuss about graphene mechanical and electrical properties and also its application in electronic industry.In short details, this review also discusses the potential application of graphene in electronic industries.